Does professionalizing maintenance unlock demand for more reliable water supply? Experimental evidence from rural Uganda. (January 2023) - Smith, Daniel W.; Atwii Ongom, Stephen; Davis, Jennifer
Highlights: A professional handpump maintenance and repair service in rural Uganda delivered fast repairs and satisfied most customer water committees. Effective demand (willingness and ability to pay) measured with real payments was lower than operational costs and decreased over time. Cross-sectional studies likely overestimate demand and may fail to identify the determinants of financial sustainability. Despite low demand, professionally maintaining all handpumps in the study area would cost less overall than letting them fail and replacing them. Governments and donors will have to pay a large share of the recurrent costs of professional services for them to be financially sustainable. Abstract: Professionalization is gaining prominence as a strategy to address the deficiencies in rural water supply reliability and financial sustainability in low- and middle-income countries that have persisted under community management policies. Yet there is little evidence regarding how much water users can and will pay for the higher reliability that professionalized services promise. What evidence exists largely relies on stated preference studies that do not confront water users with paying over time. We conducted a price experiment to measure effective demand (willingness and ability to pay) for a professional handpump maintenance and repair service among 113 water committees and 1, 031 households representative of two districts in northern Uganda. We offered a one-year subscription using Becker-DeGroot-Marschak auctions with real money payments. The service largely delivered on its guarantee of fast repairs and satisfied most customers. Nonetheless, we found that just 4% of water committees paid any price for the full service period. None paid for more than one month at prices higher than our estimate of operating cost even though it represented less than 1% of annual household expenditure. Our findings contrast assertions from recent stated preference studies that increasing handpump reliability is a lynchpin to attracting higher payments from rural water users. Misaligned incentives that discourage water users, nonprofits and their donors, local governments, and political candidates from shifting to higher tariffs for maintenance seem to best explain why effective demand was low. Despite the low demand, we estimate that professionally maintaining the existing handpumps in the study districts would cost less in the long run than the de facto practice of letting these assets fail repeatedly and rehabilitating them. As Uganda and other countries embark on maintenance-oriented, post-community management rural water policies, funders, practitioners, and researchers will need to grapple with how to align institutional incentives for sustainable financing.